A review of research on the mechanical stiffness in running and jumping: methodology and implications - Brughelli, M.; Cronin, J. (Scandinavian Journal of Medicine & Science in Sports, 2008)
Mechanical stiffness (vertical, leg and joint stiffness) can be calculated during normal human movements, such as running and hopping. Mechanical stiffness is thought to influence several athletic variables, including rate of force development, elastic energy storage and utilization and sprint kinematics. Consequently, the relationship between mechanical stiffness and athletic performance is of great interest to the sport and research communities. Unfortunately, these relationships are relatively unexplored by researchers. For example, there are no longitudinal studies that have investigated the effects of strength or power training on mechanical stiffness levels (calculated during human running). In addition to reviewing the available literature on the relationships between mechanical stiffness (calculated during human running) and functional performance, this review focuses its discussion on the various equipment and methods used to calculate leg-spring stiffness during human running. Furthermore, future implications are presented for practitioners and researchers based on both the limitations and the gaps in the literature reviewed. It is our hope that a better understanding of mechanical stiffness will aid in improving the methodological quality of research in this area and its subsequent effect on athletic performance.